Ultrastructural Localization and Molecular Associations of HCV Capsid Protein in Jurkat T Cells - Fernández-Ponce, Cecilia; Durán-Ruiz, Maria C.; Narbona-Sánchez, Isaac; Muñoz-Miranda, Juan P.; Arbulo-Echevarria, Mikel M.; Serna-Sanz, Antonio; Baumann, Christian; Litrán, Rocío; Aguado, Enrique; Bloch, Wilhelm; García-Cozar, Francisco (Frontiers in Microbiology, 2018)
Hepatitis C virus core protein is a highly basic viral protein that multimerizes with itself to form the viral capside. When expressed in CD4+ T lymphocytes, it can induce modifications in several essential cellular and biological networks. To shed light on the mechanisms underlying the alterations caused by the viral protein, we have analyzed HCV-core subcellular localization and its associations with host proteins in Jurkat T cells. In order to investigate the intracellular localization of Hepatitis C virus core protein, we have used a lentiviral system to transduce Jurkat T cells and subsequently localize the protein using immunoelectron microscopy techniques. We found that in Jurkat T cells, Hepatitis C virus core protein mostly localizes in the nucleus and specifically in the nucleolus. In addition, we performed pull-down assays combined with Mass Spectrometry Analysis, to identify proteins that associate with Hepatitis C virus core in Jurkat T cells. We found proteins such as NOLC1, PP1γ, ILF3, C1QBP implicated in localization and/or traffic to the nucleolus. HCV-core associated proteins are implicated in RNA processing and RNA virus infection as well as in functions previously shown to be altered in Hepatitis C virus core expressing CD4+ T cells, such as cell cycle delay, decreased proliferation, and induction of a regulatory phenotype. Thus, in the current work, we show the ultrastructural localization of Hepatitis C virus core and the first profile of HCV core associated proteins in T cells, and we discuss the functions and interconnections of these proteins in molecular networks where relevant biological modifications have been described upon the expression of Hepatitis C virus core protein. Thereby, the current work constitutes a necessary step towards understanding the mechanisms underlying HCV core mediated alterations that had been described in relevant biological processes in CD4+ T cells.